Por trás de uma tampinha de Coca-Cola, um mundo de coisas boas : o American way of life nas páginas de O Cruzeiro e Manchete (1950-1959) - Bammann, Kellen (2016)
As it has already been recognized in the Brazilian historiography, during the World War II there was an important American influence in Brazil, especially through the Cooperation Bureaus. The main goal behind those Bureaus was advancing the notion of “American Way of Life” to Brazilians as a soft power tool to Latin America. However, during the 1950s, the American advertising agencies that arrived in Brazil in the 1930s, were now engaged in selling this notion of an “American Dream” through their advertisements in the most popular Brazilian publications as a new tool for the Cold War. Once they fully understood and dominated the Brazilian ad market, where they masterly used a single discourse that perfectly fit the mold of the stories produced in those Brazilian magazines, which allowed those agencies to dictate the style of ad making in Brazil. In that sense, the main goal of this thesis is to analyze how the penetration of the American ad style in Brazil helped to foster the notion of “American Way of Life” in the Brazilian ad market in the postwar period. Therefore, the focus of the analysis was centered in the Coca Cola advertisement pieces that were created by the American agency McCann-Ericsson, that were publicized in the two most popular weekly Brazilian magazines from that time: O Cruzeiro and Manchete.